Prospective Analysis of EBV+ PTLD in a Multi-Center Study of Pediatric Transplant Recipients. (July 2018) - Martinez, Olivia M; Krams, Sheri M; Lapasaran, Mary Gay; Boyd, Scott D; Bernstein, Daniel; Twist, Clare; Weinberg, Kenneth; Gratzinger, Dita; Tan, Brent; Armstrong, Brian; Ikle, David; Brown, Merideth; et al.
Abstract : Post-transplant lymphoproliferative disorder (PTLD) remains a serious problem in the pediatric transplant population. The Clinical Trials of Organ Transplantation in Children (CTOT-C)-06 is an NIH-sponsored multi-institutional study intended to identify viral and immune biomarkers of Epstein-Barr virus (EBV)-associated PTLD. The laboratory studies are ongoing and herein we describe the enrolled and transplanted population to date. Enrollment began in August, 2014 and will continue until August, 2018. At the conclusion of the study all subjects will have a minimum of one year and a maximum of four years of follow-up post-transplant. As of November, 2017 there were 784 pediatric subjects enrolled and 687 children (53% male; 47% female) have received a transplant (50% liver, 22% heart, 22% kidney, 6% small intestine or multi-visceral). The mean age at transplant was 6.4 years (range 0-21 years) and 57% were EBV+, while 35% were EBV- and 8% had unknown EBV status. Of the EBV- subjects, 23% seroconverted during the study period. To date, 17 subjects (6 male, 11 female) have been diagnosed with EBV+ PTLD for an overall incidence of 2.5% (heart, n=5; kidney, n=5; liver, n=5; multivisceral, n=2). The incidence of EBV+ PTLD by organ transplanted was 3.3% in heart, 3.3% in kidney, 1.5% in liver, and 10% in multivisceral. The overall mean time post-transplant of EBV+ PTLD diagnosis was 18.9 months (range 1.7-43.9 months). The mean time post-transplant of EBV+ PTLD diagnosis by organ was 25.9 months in heart recipients, 17.8 months in kidney recipients, 19.6 months in liver recipients and 2.8 months in multivisceral recipients. Eight of the 17 patients diagnosed with EBV+ PTLD received induction medication and 10 were EBV-seronegative at transplantation. The anatomic location of disease was nodal (n=8), tonsillar (n=1) and extranodal (n=8). In summary, we report on the first large prospective US-based multi-center study on EBV+ PTLD in the era of modern immunosuppression and heightened surveillance for EB, and observe a continued incidence of EBV+ PTLD in pediatric transplant recipients. NIH 1UO1AI104342.